2012
DOI: 10.4103/0019-5154.103079
|View full text |Cite
|
Sign up to set email alerts
|

A case of fulminant varicella infection with purpura fulminans, hepatitis, and rhabdomyolysis

Abstract: Varicella zoster virus causes varicella which is a common disease. Generally it is self-limiting, and treatment is often unnecessary, but severe or life-threatening complications are rarely seen. We report a case of fulminant varicella complicating with purpura fulminans, hepatitis, and probable rhabdomyolysis in a previously healthy child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Sometimes bleeding may occur from various mucous membranes. 5,6 Disseminated varicella occurs in the neonate when the mother gets infected 1-4 days before delivery while the risk for congenital varicella syndrome is most in the first 20 weeks of pregnancy. 2,4 This syndrome is marked by limb hyperplasia, chorioretinitis, cortical atrophy, and cutaneous scars.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes bleeding may occur from various mucous membranes. 5,6 Disseminated varicella occurs in the neonate when the mother gets infected 1-4 days before delivery while the risk for congenital varicella syndrome is most in the first 20 weeks of pregnancy. 2,4 This syndrome is marked by limb hyperplasia, chorioretinitis, cortical atrophy, and cutaneous scars.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple organ failure and sepsis had occurred in patient that had thrombocytopenia. Purpura fulminans is the cutaneous manifestation of disseminated intravascular coagulation and results in microvascular thrombosis together with hemorrhagic skin and soft tissue necrosis (8). In our case, soft tissue necrosis and hemorrhages on extremities defined as purpura fulminans were dressed daily.…”
Section: Discussionmentioning
confidence: 87%
“…Some patients have developed meningoencephalitis or varicella pneumonia. [11][12][13] The incidence of AKI in rhabdomyolysis is not known, but it is estimated that between 33% and 40% of patients with rhabdomyolysis develop AKI. 14 Attempts to identify patients at highest risk of AKI have revealed that no single laboratory value, including serum CPK concentrations, can predict which patients are at risk of developing AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications may be linked specifically to the location of the VZV and not as a direct consequence of the rhabdomyolysis. Some patients have developed meningoencephalitis or varicella pneumonia 11‐13 …”
Section: Discussionmentioning
confidence: 99%